2009
DOI: 10.1002/dc.21114
|View full text |Cite
|
Sign up to set email alerts
|

Unusual microbial organisms seen in two cervical smears

Abstract: Very infrequently, unusual microbial organisms are encountered in routine cervical Pap tests. We herein report two such cases in two asymptomatic women. Case 1. A Pap smear of a 16-year-old-female showed rare glandular cells with cytologic features consistent with Cytomegalovirus infection. Case 2. A Pap smear of a 36-year-old female exhibited rare fungal organisms characterized by thin septate hyphae branching into secondary branches (metulae) which carried multiple flask-shaped philiades most consistent with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 11 publications
0
20
0
Order By: Relevance
“…Certain reports describe cervical smears where the authors conclude that the results could be due to contamination, as the other five slides exhibited the same hyphae (5,6). Additional case reports exhibited a smear test result with a description of a fruiting body in a patient (6,7).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Certain reports describe cervical smears where the authors conclude that the results could be due to contamination, as the other five slides exhibited the same hyphae (5,6). Additional case reports exhibited a smear test result with a description of a fruiting body in a patient (6,7).…”
Section: Discussionmentioning
confidence: 96%
“…Certain reports describe cervical smears where the authors conclude that the results could be due to contamination, as the other five slides exhibited the same hyphae (5,6). Additional case reports exhibited a smear test result with a description of a fruiting body in a patient (6,7). Deb and Srivastava (3) and Gupta et al (5) reported concomitant Aspergillus in patients with high-grade intraepithelial lesions, which could be explained by their immunocompromised state (3,5,9).…”
Section: Discussionmentioning
confidence: 96%
“…Awareness about such exogenous structures helps in their correct categorization and discrimination from true infection. To date, there are only seven cases of Penicillium, three cases of Aspergillus in non‐intra‐uterine device users and a single case of Cladosporium reported individually on cervical cytology in the literature. Our nine cases are the first largest case series of these unusual fungal bodies, which very well exemplifies their coexistence and the need to remain vigilant for such contaminants.…”
Section: Discussionmentioning
confidence: 99%
“…Fungal organisms like Candida are commonly seen in conventional cervical smears. Unusual and rare fungi‐like Aspergillus spp, Penicillium spp, and Cladosporium spp have been individually reported in literature in cervical smears . We report nine cases of Penicillium, Aspergillus, and Cladosporium contaminating conventional cervical smears from healthy women.…”
Section: Introductionmentioning
confidence: 90%
“…When encountered it is important to distinguish between a true infection and contamination. [25][26][27][28] A contaminated smear overrules the toxic antifungal therapy and undue follow-up, whereas true infection requires careful study of immune status and prompt therapy. 6 Aspergillus is an environmental fungus transmitted by airborne conidia.…”
Section: Aspergillus As Contaminant In Cervicovaginal Papanicolaou Smmentioning
confidence: 99%